The Relationship between Big-Five Personality Traits and Academic Achievement of Bachelor Students: A Review - Hasbi, Khairul Azhar; Jaffry, Sheril Amira; Omar, Arenawati Sehat (School of Social Sciences, USM, 2017)
Academic achievements are assessed through multiple criteria such as exams, quizzes, assignments, and personality is considered as one of the factors that contribute to attainment among students. Besides,majority of the society agreed that student’s academic achievement or performance have significant impact towards the students’ future. Most studies conducted under this topic are among different countries. Meanwhile in Malaysia, there are limited study on the relationship of Big-Five personality traits and students’ academic achievement. Therefore, the purpose of the study is to examine the relationship between Big-Five personality traits and academic achievement of degree students in UiTM Samarahan 2. Big-Five are consists of conscientiousness, extraversion, agreeableness, neuroticism and openness to experience. Not all five traits are considered as influential factors because various studies show different results between conscientiousness, agreeableness, openness to experience, extraversion and neuroticism towards academic achievement. Conscientiousness has been found by various educational researchers to be the most consistently associated or positively related with all academic achievement criteria which also lead to higher and better results. Hence, the objectives of this paper are to investigate the most dominant traits and also identify the association between Big-Five personality traits with degree students’ academic achievement in UiTM Samarahan 2. The researchers also review whether there is any gender differences in personality traits that influence academic achievement.